Relative angular precision in electron backscatter diffraction: A comparison between cross correlation and Hough transform based analysis. Issue 6 (30th May 2014) - Chekhonin, Paul; Engelmann, Jan; Oertel, Carl‐Georg; Holzapfel, Bernhard; Skrotzki, Werner
<x xml:space="preserve">Abstract</x> In the present study the relative angular resolution of an electron backscatter diffraction system based on Hough transform evaluation was determined and compared with high resolution electron backscatter diffraction. A test measurement on a BaFe2As2 thin film provides clear evidence that the angular resolution is better than 0.1°. Only in some specimen areas with strain inhomogeneities deviations are observable. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>